Atypical Hypersensitivity Reaction to Botulinum Toxin Injection - Ghorayeb, Joe; McClellan, Timithy; Crozier, Kelley (Headache Medicine, 2023)
Botulinum toxin type A (BTA) injection, marketed as BOTOX, is commonly used as a treatment for a variety of clinical indications and is widely viewed as safe, effective and largely devoid of serious side effects. Anaphylactic reactions to BTA are typically unheard of in the scientific literature. BOTOX is approved by the Food and Drug Administration for the treatment of cervical dystonia and prophylaxis for chronic migraines. This case report documents a unique instance of allergic reaction to BTA in a 29-year-old woman with cervicogenic headache and cervical dystonia who reported immediate flushing, light-headedness and nausea after receiving BTA injections.